There is no Planet B - Panayides, Angelos (My University, 2024)
Catalogue of the Exhibition of the best posters on the theme of sustainability and climate change, submitted through the festival's open call from september 9 to October 21,2024
Keywords: Visual Arts, International, Festival, exhibition